Electrochemical transformation of Prussian blue analogues into ultrathin layered double hydroxide nanosheets for water splitting - Singh B.; Prakash O.; Maiti P.; Menezes P.W.; Indra A. (My University, 2025)
Herein, we demonstrate a template directed route for the synthesis of self-supported cobalt-iron based Prussian blue analogues (PBAs). The PBAs are electrochemically transformed into layered double hydroxides to produce excellent water oxidation and hydrogen evolution activity, while the overall water splitting is attained at a cell voltage of 1.58 V to reach 20 mA cm-2 current density. This journal is © The Royal Society of Chemistry.